A importância da inovação e seus desdobramentos sobre a pesca industrial dos estados do Pará e Santa Catarina (Brasil) - SANTOS, José Nazareno Araújo dos (Universidade Federal do Pará, 2014)
Innovation is crucial to reach the socioeconomic development pursue by each country. Those that do not innovate or link innovation to their development agenda are left behind to the “centre”. This is so true, that developed countries are all more industrialized and innovative than those not developed. In Brazil this is also the case, despite being the sixth largest economy in the World, she is not a developed country, mainly because it occupies an intermediate position regarding manufacturing and innovation. This reflects throughout all activities including fisheries. Despite having a high productive potential extractive fishing when compared to other countries presents low production capacity, mainly due to the (un)willingness to adopt/develop innovative techniques that may enable a better performance. Another aspect that should be highlighted is its weak institutional capacity to promote sectorial development. In order to find alternatives to the current institutional structure of fisheries, Brazilian government, following institutional structures adopted by major fishing production countries, in 2003, adopted a new governance pattern for the sector. However, it did not change former structures. Therefore, remains relevant to identify those factors that make this important socioeconomic activity, hostage of market nuances and local circumstances that lead to inequality of the production assets of agents. In order to deeply understand it, this research in Brazilian states of Para (in the North/Amazon region) and Santa Catarina (in the South). Besides being the largest fishing producing states, are largely vulnerable to market behaviour and, at the same time present very unequal institutional frameworks and positions towards innovation. In order to compare the two states having in mind the role of innovation in the production process, an Innovative Performance Index was created based on multivariate analysis. Thus, primary data collected in the two states was submitted to a factor analysis. Results show that Santa Catarina's companies showed better results confirming the guiding hypothesis that innovation is the key to good performance at least in the fishing activity. Not forgetting that other context factors matter, including those institutional agents that closely follow domestic and international market dynamics. Another result that need to be highlighted refers to strategic skills of the entrepreneurs, that may perform better because can better cope with market complexity. Santa Catarina's entrepreneurs showed greater commitment to innovation reflected in the behaviour of their companies. These empirical results allow saying that a better integration of the institutions that coordinate agents involved in the fishing activity can create an environment that may promote a sound development of the activity and that this may apply to other sectors. This research deepened the discussion of the intricacies of innovation and its implications on development policy, allowing for strategic hints for those involved in regional and sectorial policy making.